Extracting Trading Locus: Where we are in Indo-Nepal Trade? (Nepalese Journal of Development and Rural Studies, 2020)
Nepal and India have had trade relations since time immemorial. Nepal was known as an exporting nation in the ancient times. Before the trade agreement between Nepal-Britain Treaty in1923, Nepal's trade with India was more than 95 percent. Despite various treaties and agreements between Nepal and India, Nepal's trade with India now accounts for around 65 percent of total trade. Despite the trade and mutual relations between Nepal and India, India has been treating Nepal on the basis of benefits. In different time periods, India has been creating problems in trade and transit, contrary to international norms and trade and transit treaties, under various pretexts. The objective of this paper is to review of Indo-Nepal trade and transit treaties and analyzing the present status. Descritptive and analytical research design is applied and simple statistical tools are used to analyze the growth and direction of foreign trade of Nepal. Linear regression model is applied to measure the total trade with India and total volume of foreign trade of Nepal. This study has found that there has been significant contribution of total trade with India to the total volume of foreign trade of Nepal. The import trade of Nepal with India is extremely high in comparison to export trade and total trade balance and trade balance with India has been increasing with a huge deficit.